Visible‐Light Photocatalysis as an Enabling Tool for the Functionalization of Unactivated C(sp3)‐Substrates. Issue 15 (20th February 2017) - Roslin, Sara; Odell, Luke R.
Abstract : Over the past decade, visible‐light photocatalysis has emerged as one of the brightest and most dynamic fields in modern organic chemistry. By employing a transition‐metal‐ or organic‐dye‐based photocatalyst in conjunction with a low‐energy visible‐light source, this synthetic manifold allows the facile generation of radical intermediates that can subsequently be directed through a wide range of transformations. Although initial studies focused largely on the functionalization of stabilized radical intermediates, over the past few years significant efforts have been directed towards the functionalization of challenging unactivated radical precursors. In this review we summarize the recent developments in the use of visible‐light photocatalysis for the functionalization of unactivated C(sp 3 )‐substrates. Abstract : The last few years have witnessed tremendous developments in the field of visible‐light photocatalysis. This review summarizes recent advances in the functionalization of challenging unactivated radical precursors with an emphasis on the different classes of substrates now utilizable.